The happy prince [videorecording (DVD)] - Everett, Rupert; Everett, Rupert; Everett, Rupert; Firth, Colin, 1960-; Morgan, Colin, 1986-; Thomas, Edwin, 1987- (Sony Pictures Classics, 2019)
As he lies dying in a cheap hotel in Paris, Oscar Wilde recalls his past and reflects on his relationships with his wife, Lord Alfred Douglas, and Robbie Ross.